2011
DOI: 10.1007/s10532-011-9496-7
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of tributyl phosphate by novel bacteria isolated from enrichment cultures

Abstract: Tributyl phosphate (TBP) is an organophosphorous compound, used extensively (3000-5000 tonnes/annum) as a solvent for nuclear fuel processing and as a base stock in the formulation of fire-resistant aircraft hydraulic fluids and other applications. Because of its wide applications and relative stability in the natural environment TBP poses the problem of pollution and health hazards. In the present study, fifteen potent bacterial strains capable of using tributyl phosphate (TBP) as sole carbon and phosphorus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…However, progress in this direction has been slow for the following reasons: (1) most of the strains isolated earlier had very poor efficiency of degradation (Ahire et al 2012;Berne et al 2004Berne et al , 2005Jeong et al 1994;Rosenberg and Alexander 1979;Thomas and Macaskie 1996); (2) a Pseudomonas strain, known to degrade TBP with relatively better efficiency, was unstable even when grown in the TBP-supplemented media (Thomas et al 1997); (3) few strains were not TBP degraders but merely TBP sequesters (Berne et al 2004(Berne et al , 2005; and (4) most of the strains showed a very poor tolerance to very small concentrations of TBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, progress in this direction has been slow for the following reasons: (1) most of the strains isolated earlier had very poor efficiency of degradation (Ahire et al 2012;Berne et al 2004Berne et al , 2005Jeong et al 1994;Rosenberg and Alexander 1979;Thomas and Macaskie 1996); (2) a Pseudomonas strain, known to degrade TBP with relatively better efficiency, was unstable even when grown in the TBP-supplemented media (Thomas et al 1997); (3) few strains were not TBP degraders but merely TBP sequesters (Berne et al 2004(Berne et al , 2005; and (4) most of the strains showed a very poor tolerance to very small concentrations of TBP.…”
Section: Discussionmentioning
confidence: 99%
“…In the past three decades, several bacterial strains, displaying varying TBP-degrading abilities, have been reported (Ahire et al 2012;Berne et al 2004Berne et al , 2005Chaudhari et al 2012;Kulkarni et al 2014;Rangu et al 2014;Rosenberg and Alexander 1979;Thomas and Macaskie 1996). Among these, the Sphingobium sp.…”
Section: Introductionmentioning
confidence: 99%
“…[3,26,27]. Recently, very efficient degradation of TBP by bacterial strains was reported [1,11]. Efficient and complete degradation of 2 mM of TBP with a degradation rate of 0.25 mol mL −1 h −1 was achieved using Sphingobium sp.…”
Section: Biodegradation Of Tributylphosphatementioning
confidence: 99%
“…Biological treatment of TBP bearing wastes is attractive because it does not generate secondary wastes and may be less expensive. TBP can be mineralized by mixed cultures of bacteria [9,10] or by defined bacterial cultures [1,2,9,11,12]. Pure bacterial cultures such as Acinetobacter sp., Serratia odorifera, Prodencia sp., Delftia sp., Pseudomonas pseudoalkaligenes and Sphingobium have been reported to degrade TBP.…”
Section: Introductionmentioning
confidence: 99%
“…Although plant growth promotion rhizobacteria are commonly used to promote plant growth and control plant diseases, their potential use in bioremediation has also been explored (Narasimhan et al, 2003;Huang et al, 2005). Several studies have been conducted to isolate pure bacterial strains with degrading capability for potential uses such as the removal of glyphosate from soil and bioremediation of glyphosate-contaminated soils (Ermakova et al, 2008;Ahire et al, 2012;Kryuchkova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%